Human Adipose Derived Cells in Two- and Three-Dimensional Cultures: Functional Validation of an In Vitro Fat Construct. (10th June 2020) - Bender, Robert; McCarthy, Michelle; Brown, Theodore; Bukowska, Joanna; Smith, Stanley; Abbott, Rosalyn D.; Kaplan, David L.; Williams, Christopher; Wade, James W.; Alarcon, Andrea; Wu, Xiying; Lau, Frank; et al.
Abstract : Obesity, defined as a body mass index of 30 kg/m 2 or above, has increased considerably in incidence and frequency within the United States and globally. Associated comorbidities including cardiovascular disease, type 2 diabetes mellitus, metabolic syndrome, and nonalcoholic fatty liver disease have led to a focus on the mechanisms promoting the prevention and treatment of obesity. Commonly utilized in vitro models employ human or mouse preadipocyte cell lines in a 2-dimensional (2D) format. Due to the structural, biochemical, and biological limitations of these models, increased attention has been placed on "organ on a chip" technologies for a 3-dimensional (3D) culture. Herein, we describe a method employing cryopreserved primary human stromal vascular fraction (SVF) cells and a human blood product-derived biological scaffold to create a 3D adipose depot in vitro. The "fat-on-chip" 3D cultures have been validated relative to 2D cultures based on proliferation, flow cytometry, adipogenic differentiation, confocal microscopy/immunofluorescence, and functional assays (adipokine secretion, glucose uptake, and lipolysis). Thus, the in vitro culture system demonstrates the critical characteristics required for a humanized 3D white adipose tissue (WAT) model.